Metabolite identification in different fractions of Ficus auriculata Loureiro fruit using the 1H-NMR metabolomics approach and UHPLC-MS/MS - Mohamed Yunus, Siti Norhamimah; Zolkeflee, Nur Khaleeda Zulaikha; Jaafar, Ahmad Haniff; Abas, Faridah (Elsevier BV, 2021)
Ficus auriculata Loureiro is one of the neglected fruits in Malaysia, which has been traditionally claimed to have health promoting benefits. However, scientific studies that prove the biological activities and metabolites profile of this fruit are lacking. Therefore, the current study aimed to provide a better insight into the variation of different fractions of F. auriculata fruit, that is, hexane (HF), dichloromethane (DF), ethyl acetate (EF), butanol (BF) and aqueous (AF). This study also aimed to examine the correlation of the metabolite content with the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide (NO) radical scavenging activities, and α-glucosidase inhibitory activity through a robust 1H-nuclear magnetic resonance (1H-NMR) metabolomics approach. The biological activity results showed that EF was the most active fraction toward DPPH and NO radical scavenging activities (IC50 values of 6.21 and 93.79 µg/mL, respectively), followed by DF and HF, which were revealed to have higher α-glucosidase inhibitory activities (IC50 values of 2.90 and 2.52 µg/mL, respectively) than the other fractions. A total of 37 and 77 metabolites were tentatively identified through NMR and UHPLC-MS/MS analyses, respectively. The metabolites that have been observed to contribute to antioxidant and α-glucosidase inhibitory activities were quercetin, catechin, caffeic acid, apigenin, chlorogenic acid, lupeol, and lupeol acetate and oleic acid, linoleic acid, linolenic acid, lupeol acetate and betulinic acid, respectively. The results of the present study indicated that the different solvent fractions exhibited variations in the recovery of metabolites that have high antioxidant and α-glucosidase inhibitory activities in F. auriculata fruit.